Social capital, intellectual capital, and audit fee: Conflicting evidence from Iran - Hossein Tarighi; Mahdi Salehi; Mahdi Moradi; Grzegorz Zimon (Economies, 2022)
In the current study, we investigate the impacts of social capital (SC) and intellectual capital (IC) on audit fees among the companies listed on the Tehran Stock Exchange (TSE). Since the criteria for the norms and the networks are extremely correlated, we used a principal component analysis (PCA) to construct an index of social capital for each province between 2011 and 2016. The Pulic model is also used as a proxy for measuring value added intellectual capital (VAIC). The ordinary least squares (OLS) regression is employed in this study to test our research hypotheses as well. According to the research literature, on the one hand, investors and lenders can be more confident in the financial reporting honesty of the firms headquartered in areas with high social capital; on the other hand, auditors judge the trustworthiness of their clients based on where the firm is headquartered. Inconsistent with the prior studies, our findings show that companies headquartered in provinces with high social capital pay higher audit fees. Given that Iranian firms are under heavy financial pressure due to economic sanctions, those companies located in areas with higher social capital likely have abused the high level of trust that auditors and other groups in the market have in them and participated in earnings manipulation to mask their weak financial performance. Among the various components of IC, we found strong evidence that employed capital efficiency (ECE) and audit costs correlated positively. In short, this paper sheds light on the fact that severe financial pressures on managers may sometimes lead them to take advantage of the dark side of social capital and intellectual capital when preparing financial reports.
Keywords: 330; audit fee; employed capital efficiency; human capital efficiency; intellectual capital; networks; norms; social capital; structural capital efficiency; Tehran stock exchange